(untitled) (CIPEEX, 2023)
To ensure the integrity of the experiments in obtaining photoprotection of the API (Active Pharmaceutical Ingredient) ciprofloxacin, a Risk Analysis was conducted to identify the possible risks associated with the mixture of ciprofloxacin with the excipient curcumin in the respective proportions of 1/1, 1/0.5, and 2/1. Within this evaluation, it was possible to define the critical and non-critical attributes of the API that could interfere with the experiments. The methodology adopted to obtain the results followed the guidelines of the ICHQ9 Guide from January 2023, and the risk assessment of each attribute within the experiment was based on the information provided by the IFA manufacturer, Sigma-Aldrich, and data evidenced in the literature. According to the risk analysis, the only attribute considered critical for the experiment was the active ingredient content, which has a potency different from 100%, and its mass was adjusted so that the proportion between the mixtures of raw materials could be corrected.